I Did It, But…: Exploring DUI Offender Deviance Rationalization in the Digital Age. Issue 10 (3rd October 2022) - Tatch, Andrew
ABSTRACT: The dangers associated with alcohol-impaired driving are well documented, most recently stabilizing at still problematic levels around 2010. Recent estimates indicate over 1 million annual DUI arrests. Researchers have primarily adopted quantitative approaches to identify common predictors of impaired driving. Few studies have systematically examined this group using qualitative data, specifically how they process the heavily stigmatized arrests and none have specifically examined these processes in online spaces. To fill this gap, a qualitative content analysis was conducted on over 600 DUI narratives from reddit. This study documents the stigmatizing effects of a DUI arrest and explores the utility of accounts and techniques of neutralization in negotiating impaired driving on a digital stage. Analyses suggest offenders utilize multiple strategies to deflect full culpability for their arrest, performing impression management through excuses, justifications, and techniques of neutralization to minimize responsibility for driving impaired, the reason for police contact, failed field sobriety tests, or illegal blood alcohol concentrations. These insights provide additional support for the utility of easily accessible online data as a fruitful arena for analyses of contemporary social problems.